Comparative investigations on sulfidic gold ore processing: A novel biooxidation process option. (15th August 2019) - Ahn, Junmo; Wu, Jiajia; Ahn, Jaewoo; Lee, Jaeheon
Highlights: Gold was associated with pyrite, tennantite, or enargite in sulfidic refractory ores. Gold occurs as native gold, with calaverite, petzite, hessite, and goldfieldite. Gravity concentration didn't work well but flotation worked fine. Tank biooxidation recovered gold up to 96.6%. Coarser ground Sand Farming biooxidation works very well with up to 96.0% and can be used for alternative to POX or Roasting. Abstract: Microbial enhanced sulfide oxidation is one of the alternatives to roasting or pressure oxidation (POX). High grade whole ores or upgraded sulfide concentrates can be processed using POX or roasting processes but the high capital and operating costs often prohibit to process lower grade materials using these process methods. Sand Farming process is a novel alternative to POX or roasting for medium to low grade materials. The key advantage of the process is to use a relatively coarser material compared to POX or roasting. The POX and roasting processes utilize fine ground materials with P80 75 µm or smaller to achieve higher gold recovery. The Sand Farming process uses agglomerated sample of P80 0.60 mm and the comminution cost saving is significant. Ore samples were collected from a gold mine in Mexico and two metallurgical composites were prepared for the study. Comp #1 contains 2.7 g/t of gold and 15.4 g/t of silver with 0.33% copper and 0.11% arsenic. The total sulfur was 5.7% and the sulfide sulfur was 5.6%. Gold and silver grade of Comp #2 was 1.2 g/t and 8.8 g/t, respectively. Copper and arsenic concentrations were lower than 0.07% and 0.03%. Total sulfur was 5.0% with 4.9% sulfide sulfur. The gold recovery from the Sand Farming was comparable to POX and roasting. Roasting calcine yielded the gold extraction of 70% while gold extraction from POX residue showed about 90%. After 44 days of Sand Farming biooxidation, 80% and 90% gold extractions were observed from Comp #1 and Comp #2, respectively. The gold extractions were further increased to 92% and 96% after 83 days of biooxidation.